2016
DOI: 10.2147/hmer.s98120
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: a new target for nonalcoholic fatty liver disease therapy

Abstract: Nonalcoholic fatty liver disease (NAFLD) has gained importance in recent decades due to drastic changes in diet, especially in Western countries. NAFLD occurs as a spectrum from simple hepatic steatosis, steatohepatitis to cirrhosis, and even hepatocellular carcinoma. Although the molecular mechanisms underlying the development of NAFLD have been intensively investigated, many issues remain to be resolved. Autophagy is a cell survival mechanism for disposing of excess or defective organelles, and has become a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 97 publications
1
69
0
1
Order By: Relevance
“…Autophagy plays a pivotal role not only in normal liver physiology, but also in the pathogenesis of many liver diseases including nonalcoholic and alcoholic fatty liver and viral hepatitis (Mao et al 2016; Tang et al 2012). Acute T. cruzi infection may adapt lipophagic pathway to survive energy starvation by increasing autophagic sequestration of lipid droplets and their degradation in hepatic lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy plays a pivotal role not only in normal liver physiology, but also in the pathogenesis of many liver diseases including nonalcoholic and alcoholic fatty liver and viral hepatitis (Mao et al 2016; Tang et al 2012). Acute T. cruzi infection may adapt lipophagic pathway to survive energy starvation by increasing autophagic sequestration of lipid droplets and their degradation in hepatic lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that autophagy, a cell survival mechanism for disposing of excess or defective organelles, is linked to the development of NAFLD and the regulation of autophagy has potential therapeutic effects. Autophagy reduces intracellular lipid droplets by enclosing them and fusing with lysosomes for degradation and is involved in attenuating inflammation and liver injury . To investigate whether EGCG regulates autophagy and then improves the lipid clearance in the liver, Zhou et al .…”
Section: Basic Researchmentioning
confidence: 99%
“…EGCG treatment was also shown to reduce hepatosteatosis and concomitantly increases autophagy in the livers of mice fed with a high‐fat/Western‐style (HFW) diet. Nevertheless, autophagy is regarded as a double‐edged sword, its potential effects on adipogenesis, adipocyte differentiation, as well as the association between autophagy and NAFLD remain controversial …”
Section: Basic Researchmentioning
confidence: 99%
“…Autophagy is considered of crucial importance in liver metabolism. Autophagy degrades and recycles protein and cell organelles supplying amino acids to cellular processes, delivers glycogen to vacuoles during starvation, and breaks down lipid droplets, providing free fatty acids and intracellular triglycerides 1‐3 . Several studies have shown that hepatic autophagy is dysregulated in metabolic liver diseases such as nonalcoholic fatty liver disease and obesity 4 …”
Section: Introductionmentioning
confidence: 99%